The Paradigm of the Effective Factors in the Process of the Writings of The Quran Sciences (6th Century to 10th Century) in the Form of Grounded Theory - Najmeh Najm; Mahdi Mehrizi Toroqi; Muhammad Ali Mahdavi Rad; Sayyed Muhammad Ali Ayazi (آموزه‌های قرآنی)
The present paper studies from the approach of the social, scientific and thoughtful interpretivism to the perception and analysis of the effective factors in the development of the Quran science writings. It has been studied the eight books of the Quran sciences from the sixth century to the tenth century with the condition that they were effective in their periods. The documentary method and the historic analysis has been used for the process of the research and it has been used Grounded theory (GT) for analyzing and examining information. The obtained findings which have contained the eighteen categories in the evolution have been stated with the separation of factors with the high impact factor, medium impact factor and low impact factor. Also the final paradigm of the effective factors in the development of the Quran science writings have been mentioned in the form of Grounded theory (GT) and its components are: causative factors including the individual’s personality of the author, the scientific expertise of the author, the social and cultural factors of author’s period, the author’s companions and his effectiveness of bibliographies and previous authors and his impact on the next bibliographies and authors, the identity and originality of the written text (including structure, function and content). The background factors such as the circumstances of time and geographic location, the several immigration and travels of the author, the comprehensiveness of the source titles, the oldness and notability of the writing and author. The mediator factors such as the ethical personality of the author, political and economic factors of his time, the author’s free thought and liberty or prejudice. Also it has been stated the obtained strategies and consequences.